ANALISIS STRUKTUR MODAL PADA PERUSAHAAN-PERUSAHAAN NON FINANSIAL YANG GO PUBLIC DI PASAR MODAL INDONESIA - Mutamimah, Mutamimah (JURNAL BISNIS STRATEGI, 2003)
The suitable capital structure is very important for firms to increase their performance. Capital structure theory until now still debatable. The main objective of this study is to investigate empirically the determinants of capital structure with Trade-off Theory, Pecking Order Theory, and Agency Theory Approach.Sample in this study are 50 non-financial firms that active and liquid at Indonesian Capital Market over 2 (two) years, from 1999 to 2000. Thus, I have 100 observations. Non financial firms are choose to prevent bias result,because commonly financial firms have unique financial ratio, for example high leverage ratio. To test the hypotheses in this study, I used Multiple Regression Models. Â·The result of this study as follows: a). Simultaneously and partially all proxy of Trade-off Theory isn't significant statistically. Thus, Trade-off Theory can't explain the capital structure at Indonesian Capital Market b). Simultaneously proxy of Pecking Order Theory can explain capital structure at Indonesian Capital Market. c). Simultaneously proxy of Agency Theory can explain capital structure at Indonesian Capital Market. d). Firms that go public at Indonesian Capital Market tend to follow Pecking Order Theory and Agency Theory than Trade-off Theory in their financing decision. Part of result in this study is consistent with study of Sartono (2001), Taggart (1977), Marsh (1982), and Wiwattanakantang (1999).